2017
DOI: 10.1017/s1360674316000447
|View full text |Cite
|
Sign up to set email alerts
|

Ditransitives in Middle English: on semantic specialisation and the rise of the dative alternation

Abstract: This article discusses the plausibility of a correlation or even a causal relation between two phenomena that can be observed in the history of English ditransitives. The changes concerned are: first, the emergence of the ‘dative alternation’, i.e. the establishment of a link between the double object construction (DOC) and its prepositional paraphrase, and second, a reduction in the range of verb classes associated with the DOC, with the construction's semantics becoming specialised to basic transfer senses. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 41 publications
1
33
0
1
Order By: Relevance
“…In the remainder of this article, we demonstrate how such an enterprise may be carried out, using the wellknown box formalism of Construction Grammar (cf. also Barðdal & Eythórsson 2012b, Barðdal & Smitherman 2013, Danesi, Johnson & Barðdal 2017, 2018.…”
Section: The Syntactic Reconstructionmentioning
confidence: 99%
“…In the remainder of this article, we demonstrate how such an enterprise may be carried out, using the wellknown box formalism of Construction Grammar (cf. also Barðdal & Eythórsson 2012b, Barðdal & Smitherman 2013, Danesi, Johnson & Barðdal 2017, 2018.…”
Section: The Syntactic Reconstructionmentioning
confidence: 99%
“…Compared to traditional CxG approaches, the allostructional approach assumes that the alternation does have independent status ( Zehentner, 2018 : 169). Even though this approach has increasingly been adopted in constructionist research ( Perek, 2012 , 2015 ; Zehentner, 2016 , 2018 ; De Vaere et al, 2018 , De Vaere et al, 2021 , Willems et al, 2019 ) many open questions remain. We will focus here on questions regarding the meaning side of the constructional sign, the details of which we turn to next.…”
Section: Alternating Constructions In Cxg and The Idea Of Allostructimentioning
confidence: 99%
“…Following Cappelle, various other authors working within CxG have demonstrated the viability of the allostructional analysis by applying it to numerous other alternations, e.g. the dative alternation and the locative alternation in present-day English ( Perek, 2015 ), as well as the dative alternation in Middle English ( Zehentner, 2016 , 2018 ) and the ditransitive alternation in present-day German ( De Vaere et al, 2018 , De Vaere et al, 2021 , Willems et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Since its emergence in the 1970s [ 36 , 39 , 40 ], EGT has reached a level of maturity in the fields of mathematical biology and economics. As several authors have noted, however, this framework is also applicable to the modelling of language dynamics, if its ingredients are suitably interpreted [ 26 35 ]. In general, it is possible to equate strategies with linguistic variants, i.e.…”
Section: Evolutionary Games and Language Dynamicsmentioning
confidence: 99%
“…A number of applications of evolutionary game-theoretic (EGT) modelling are now available in the literature on language dynamics [ 26 35 ]. These will be briefly discussed in § 2 in order to contextualize the contribution of the present paper.…”
Section: Introductionmentioning
confidence: 99%